A three-electrode structured ionic polymer carbon-composite actuator with improved electromechanical performance. (10th July 2018) - Bian, Changsheng; Ru, Jie; Zhu, Zicai; Bin Luo,; Chen, Hualing
Abstract: Ionic polymer carbon-composite (IPCC) is a kind of ionic electroactive polymer with a Nafion/ionic liquid electrolyte layer between two multi-walled carbon nanotube (MWCNT) film electrodes. We have fabricated a three-electrode structured IPCC (3E-IPCC) that exhibited a higher safe working voltage and improved electromechanical performance when compared with a traditional two-electrode laminar actuator. An intermediate electrode that was fabricated using MWCNTs was introduced into the matrix membrane, which was then subjected to hot-pressing to form the 3E-IPCC actuator. The effects of the intermediate electrode on the performance of the 3E-IPCC were analyzed. The experiment results indicated that the intermediate electrode connected the two electrolyte layers in series and successfully broadened the window of working voltage by distributing the voltage over the two electrolyte layers. The broadened window of working voltage endowed a higher safe working voltage and then led to enhanced electromechanical performance when compared with the traditional IPCC actuator. The 3E-IPCC exhibited desirable properties, including a large deformation, high output force and excellent stability under high working voltages and so these actuators show great potential for use in a wide range of fields.